2009
DOI: 10.1211/jpp.61.12.0013
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidaemic activity of orally administered diphenyl diselenide in Triton WR-1339-induced hyperlipidaemia in mice

Abstract: These findings indicated that (PhSe)(2) was able to lower plasma lipid concentrations. Further studies are needed to elucidate the exact mechanism by which (PhSe)(2) exerted its hypolipidaemic effect in the management of hyperlipidaemia and atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 52 publications
3
22
1
Order By: Relevance
“…To screen the hypolipidemic effect of natural or chemical drugs, Triton WR-1339 (Sigma-Aldrich, St. Louis, MO, U.S.A.) has been widely used to induce acute hyperlipidemia in animal models in doses ranging from 200 to 400 mg/kg. 15) In this study a dose of 300 mg/kg of Triton WR-1339 dissolved in water was given intraperitoneally to the rats. 16) Pharmacological Experimental Design Overnight forty-eight fasted rats were randomly divided into six groups each consisting of eight animals.…”
Section: Induction Of Hyperlipidemia By Triton Wr-1339mentioning
confidence: 99%
“…To screen the hypolipidemic effect of natural or chemical drugs, Triton WR-1339 (Sigma-Aldrich, St. Louis, MO, U.S.A.) has been widely used to induce acute hyperlipidemia in animal models in doses ranging from 200 to 400 mg/kg. 15) In this study a dose of 300 mg/kg of Triton WR-1339 dissolved in water was given intraperitoneally to the rats. 16) Pharmacological Experimental Design Overnight forty-eight fasted rats were randomly divided into six groups each consisting of eight animals.…”
Section: Induction Of Hyperlipidemia By Triton Wr-1339mentioning
confidence: 99%
“…In fact, the effects of (PhSe) 2 on lipid profile is dependent of the experimental model used. For example, we observed that (PhSe) 2 was able to decrease the plasma cholesterol levels in rabbits fed with cholesterol diet as the oral treatment with (PhSe) 2 had a hypolipidaemic effect in Triton WR‐1339‐induced hyperlipidemia in mice . On the other hand, in this hypercholesterolemic mice model, we did not observe any changes in lipid profile after (PhSe) 2 treatment; then we can suppose that the anti‐atherogenic effect of this compound can be related to its effective antioxidant property.…”
Section: Discussionmentioning
confidence: 77%
“…Several reviews from our laboratory have focused on this topic [159-161]. Briefly, organoselenium compounds have been shown to possess glutathione peroxidase-mimetic activity [162-166], lipid peroxidation/radical-scavenging/peroxynitrite-scavenging activity [167-171], thioredoxin reductase-like activity [172-176], antiinflammatory and antinociceptive activity [177-181], antinociceptive activity [182-186], hepatoprotective activity [187-191], gastroprotective activity [192-196], nephroprotective activity [197-201], cardioprotective activity [202-206], insulin-mimetic activity [207-211], and neuro-protective activity [212-218] (Scheme 3 ).…”
Section: Future Directionsmentioning
confidence: 99%